Aristotle for nursing. (25th July 2016) - Allmark, Peter
Abstract: This article aims: (1) to introduce the wider philosophy of Aristotle to nurses and healthcare practitioners; (2) to show that Aristotle's philosophical system is an interdependent whole; and (3) to defend its plausibility and usefulness despite its ancient and alien origins. Aristotle's system can be set out as a hierarchy, with metaphysics at the top and methodology running throughout. Beneath metaphysics are the sciences, with theoretical, practical and productive (or craft) sciences in hierarchical order. This hierarchy does not imply that, say, metaphysics is superior to biology or nursing, but rather that metaphysics can be understood without reference to the other two but, as we shall see, not vice versa . Two themes run through Aristotelian philosophy. The first is Aristotle's method of inquiry, central to which is that our starting point is not pure empirical data, but rather current puzzles; complementing this method is a realist philosophy. The second theme is teleology, the understanding of action in the world in terms of ends, as when we say a plant grows roots to reach water and nutrients. Implications for nursing . Good health is the good functioning of the material aspect of humans; flourishing is good functioning of humans per se . The goals of nursing, which are based on health, are subsumed by the overall human goal of flourishing, and this helps us to understand and set boundaries to health care. Two examples illustrate this. The first is that mental illness is strongly within the purview of nursing and health care whereas bad decisions, such as smoking, are only marginally so. The second is ethics, where it is argued that the attempt to describe ethical decision‐making as in addition to and separate from the decisions made within nursing and health care itself cannot be sustained.